Value Added Tax : International Practice and Problems - Tait, Alan (International Monetary Fund, 1988)
This book, by Alan A. Tait, is an examination of VAT. It looks at problems and theoretical options and potential impacts, as well as detailing the practical aspects of implementing new tax structures. The author advances arguments for and against alternative policies and illustrates his study with international examples from Europe, Latin America, Asia, and the Pacific. He suggests that countries can learn from each other's experiencees with VAT.